Use of electronic cigarettes as a risk factor for the different clinical outcomes of COVID-19: A systematic review (Research, Society and Development, 2023)
Objectives: The objective of this study is to systematically review the available epidemiological research published between January and December 2020 in PubMed, Scielo, and LILACS to determine the role of electronic cigarettes as a risk factor for different clinical outcomes of COVID-19. Methods and Material: Systematic review of epidemiological studies published, from January to December 2020, in PubMed, Scielo and LILACS. Registered with PROSPERO, under code: CRD42020226931. Results: Two studies that met the inclusion criteria were included in this review. Both studies were observational and cross-sectional in design. The combined sample size of the studies was 7530 individuals. The results indicated statistically significant associations between electronic cigarette use and COVID-19. When compared to individuals who never used tobacco products, chronic users of e-cigarettes alone were found to be 5.05 times more likely to test positive for COVID-19 (CI 1.82 - 13.96). Similarly, individuals who used both electronic and conventional cigarettes were 6.97 times more likely to test positive for COVID-19 (CI 1.98 - 24.55). Among self-reported infected or previously infected individuals, those who consistently used electronic cigarettes had a 1.30 times greater chance of becoming infected (CI 0.91 - 1.81), while individuals who used both types of smoking had a 1.44 times higher likelihood of infection (CI 1.13 - 1.84). Notably, stronger associations were found for individuals who reported using both electronic and conventional tobacco products, particularly within the last 30 days. Conclusion: There was a positive association between a positive test for COVID-19 and self-reported infection with e-cigarette use.